Environmental history of postcolonial north India: the Himalayan tarai in Uttar pradesh and Uttaranchal - Strahom, Eric A. (New York, 2009)
An Environmental History of Postcolonial North India is a study of an increasingly important part of the Indian landscape. It examines the social process of accelerated land use as it has been affected by political and epidemiological factors and pays particular attention to the shifting representations of the landscape. As a contribution to the literature of the environmental history of India, this book examines the questions of agricultural colonization, wildlife conservation, and disease control.
Keywords: Tarai-Environmental conditions